Inovasi Pengembangan Kurikulum Berbasis 21st Century Learning Design untuk Pembelajaran IPAS - Siti Raihan (Departement of Mathematics Education, 2024)
Educational transformation in line with the demands of the times is continuously implemented, one of which is through the adoption of the Merdeka Curriculum. The implementation of the Merdeka Curriculum still requires innovation in the development of a 21st-century learning design-based curriculum to facilitate lifelong learning. This literature review research aims to uncover and explore the potential innovations that can be applied in the development of a technology-based curriculum with the 21CLD approach, in order to contribute to a better and more relevant educational transformation that meets the needs of students in the digital era, particularly in the implementation of IPAS (Science and Social Studies) learning. The findings of this study reveal that educators need to develop learning designs that facilitate creative thinking, critical thinking and problem-solving, communication, and collaboration skills that lead to long-term memory for lifelong skills. Innovations that can be implemented by educators in IPAS learning include the development of innovative learning designs, using problem-based and project-based learning models, which refer to active and enjoyable learning, such as gamification. In addition, the integration of technology and continuous assessment should be conducted to optimize the implementation of learning by educators.